Proposed Marketing Strategy MuFiNs Brownies (The Indonesian Journal of Business Administration, 2015)
Abstract. MuFiN is one of the small and medium enterprises in food product in Bandung. With their main product is steamed brownies. MuFiN is also selling various kinds of cakes and pastry products. MuFiN has been in the business since 2010, and it has 15 branches spread all over the Bandung City and in several cities such as Garut, Cirebon, and Tasikmalaya. To survive from competitors, MuFiN wants to expand their business scope. With their expertise in bakery field MuFiN plans to make more innovation and creation for their product. By doing so, MuFiN can focus on meeting all the consumer needs for bakery products.To meet all consumer needs and preferences, first MuFiN should understand the consumer current needs. To provide a business solution, we started from analyzing the external analysis consists PEST analysis, porterâ€Ÿs five forces, competitor analysis and consumer behavior analysis. The internal analysis consist STP analysis and marketing mix 7P. The analysis of consumer behavior obtained from questionnaires directly to respondents who consume bakery product in Bandung. The analysis of consumer behavior includes the purchase decision, TIMES models analysis, consumer motivations and needs for bakery products. TIMES model approach is used for the analysis of external factors, especially from consumer side to know and understand the customer from some part of which is time, information, money, energy, and space. From the results of internal and external analysis, we can conclude and evaluate using SWOT analysis. The result of SWOT analysis is used for make alternative strategy based on TOWS Matrix. After deciding strategy, we proposing a new marketing strategy can be run by MuFiN.Keywords: Marketing Strategy, Bakery, Consumer Preferences, TIMES modelÂ